1993
DOI: 10.1007/bf02536319
|View full text |Cite
|
Sign up to set email alerts
|

Identification of core aldehydes amongin vitro peroxidation products of cholesteryl esters

Abstract: Synthetic cholesteryl 5-oxovalerate and 9-oxononanoate were used as reference standards for the isolation and identification of cholesteryl ester core aldehydes from tert-butyl hydroperoxide/Fe++ oxidation of synthetic and natural cholesteryl esters. The core aldehydes were recovered from the peroxidation products by thin-layer chromatography as the free aldehydes or the 2,4-dinitrophenylhydrazones and were identified, respectively, by gas-liquid chromatography (GLC) and by GLC combined with mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 22 publications
5
55
0
Order By: Relevance
“…Work is currently under way to identify the molecular structure of these phospholipids. It has previously been shown that Ox-LDL contains cholesterolbound aldehydes, the carbonyl function of which is predominately associated with the most proximal carbon involved in a double bond (i.e., cholesteryl-arachidonate results in cholesteryl-5-oxovalerate and cholesteryl-linoleate results in cholesteryl-9-oxononanoate) (47). If this is a general phenomenon of esterified PUFA, one might expect the predominate phospholipid-bound aldehydes in LDL to be l-acyl-2(5)-oxovaleroylsn-glycero-3-phosphorylcholine and 1-acyl-2 (9) -oxononanoylsn-glycero-3-phosphorylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…Work is currently under way to identify the molecular structure of these phospholipids. It has previously been shown that Ox-LDL contains cholesterolbound aldehydes, the carbonyl function of which is predominately associated with the most proximal carbon involved in a double bond (i.e., cholesteryl-arachidonate results in cholesteryl-5-oxovalerate and cholesteryl-linoleate results in cholesteryl-9-oxononanoate) (47). If this is a general phenomenon of esterified PUFA, one might expect the predominate phospholipid-bound aldehydes in LDL to be l-acyl-2(5)-oxovaleroylsn-glycero-3-phosphorylcholine and 1-acyl-2 (9) -oxononanoylsn-glycero-3-phosphorylcholine.…”
Section: Discussionmentioning
confidence: 99%
“…The oxLDL and acetylated LDL had 2-3-fold higher R f values on agarose gel electrophoresis compared with the native LDL. Gas chromatography (45) revealed that a typical preparation of ox LDL contained 4.0 g of 7␣-hydroxycholesterol/mg of LDL protein, 13.1 g of epoxide/mg of LDL protein, 14.9 g of 7-keto-cholesterol/mg of LDL protein, and 1.1 mg of unidentified oxycholesterol/mg of LDL protein.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported on the identification of high molecular weight secondary products of peroxidation of standard lipids and lipoproteins during in vitro incubation with tert-butyl hydroperoxide [1,2] or copper ions [3,4]. Using these products as reference standards we have identified lipid ester hydroperoxides and core aldehydes in plasma and atheromas of patients with atherosclerosis and diabetes [5].…”
Section: Introductionmentioning
confidence: 99%
“…All chemicals were of reagent grade quality, while the solvents were of chromatographic purity and were obtained from local suppliers. The purity of the reference compounds was ascertained by thin-layer chromatography (TLC) [3,7]. …”
mentioning
confidence: 99%